Epilepsy Surgery: The Patient's Perspective. (16th November 2020) - Telemi, Edvin; Mansour, Tarek R; Sion, Amanda; Gilbert, Jennifer; Air, Ellen L
Abstract: INTRODUCTION: Surgical resection can offer select patients with refractory epilepsy seizure freedom in 50–70% of cases. However, surgery remains highly underutilized. Understandably, undergoing brain surgery can be intimidating and many good surgical candidates ultimately decline surgery. Therefore, it is necessary to understand the factors most important to patients in their decision to undergo or decline surgery. In this study we sought to identify those factors and shed light onto patient's decision-making process. METHODS: We surveyed 16 patients with history of seizures undergoing monitoring in our epilepsy monitoring unit. The survey was limited to surgery naïve patients. We developed a novel rank list questionnaire that addressed a variety of potential social, economic, medical, and personal factors. Patients were asked to rank the factors in order of importance to their decision making regarding undergoing brain surgery if offered as a treatment option for their epilepsy. RESULTS: The average age of those surveyed was 42 and average age of seizure onset was 24. Frequency of seizures ranged from none to 7 per day. Nine patients were currently taking 1 antiepileptic medication, and seven were taking 2 or more medications. On average patients had tried and discontinued approximately 3 other medications. Among the factors that patients considered most important when deciding on surgery were the likelihood of seizure freedom, ability to again drive, and likelihood of complications such as motor, sensory, speech and memory deficits. Factors considered least important included time commitment and discomfort associated with surgery. CONCLUSION: Surgical intervention can offer well selected patients a relatively high likelihood of seizure freedom that can significantly improve their quality of life. However, about 30–40 percent of surgical candidates declined surgery. Gaining a better understanding of the factors that play an important role in patient's decision making regarding surgical management of their epilepsy can empower their provider to address and mitigate those concerns.